The Effect of Motive‐Trait Interaction on Satisfaction of the Implicit Need for Affiliation Among German and Cameroonian Adults. Issue 2 (6th March 2014) - Hofer, Jan; Busch, Holger; Schneider, Carolin
Abstract: Research provided evidence that personality traits influence the realization of implicit motives: Extraversion supported the successful realization of the implicit motives for affiliation and power, whereas introversion deflected implicit motives away from significant goals and created difficulties in goal attainment. Based on those findings on motive‐trait interaction, we tested whether the traits of Neuroticism, Agreeableness, and Extraversion affect the satisfaction of the implicit affiliation motive (i.e., the need for establishing and maintaining close relationships with other people) approximately 18 months later. Data on personality traits, the implicit affiliation motive, and need satisfaction were assessed from 244 Cameroonian and German adults. As expected, across cultural groups, Neuroticism constrains but Agreeableness supports the realization of the implicit affiliation motive. No significant results could be found for Extraversion, even if the effect was in the assumed direction. The findings support the argument that different significant personality components ought to be taken into account in research on implicit motives and their psychological and behavioral correlates.